Chinese guideline on the application of anti-seizure medications in the perioperative period of supratentorial craniocerebral surgery. (August 2022) - Liang, Shuli; Fan, Xing; Chen, Feng; Liu, Yonghong; Qiu, Binghui; Zhang, Kai; Qi, Songtao; Zhang, Guojun; Liu, Jinfang; Zhang, Jianguo; Wang, Jun; Wang, Xiu; et al.
Seizures are a common symptom of craniocerebral diseases, and epilepsy is one of the comorbidities of craniocerebral diseases. However, how to rationally use anti-seizure medications (ASMs) in the perioperative period of craniocerebral surgery to control or avoid seizures and reduce their associated harm is a problem. The China Association Against Epilepsy (CAAE) united with the Trauma Group of the Chinese Neurosurgery Society, Glioma Professional Committee of the Chinese Anti-Cancer Association, Neuro-Oncology Branch of the Chinese Neuroscience Society, and Neurotraumatic Group of Chinese Trauma Society, and selected experts for consultancy regarding outcomes from evidence-based medicine in domestic and foreign literature. These experts referred to the existing research evidence, drug characteristics, Chinese FDA-approved indications, and expert experience, and finished the current guideline on the application of ASMs during the perioperative period of craniocerebral surgery, aiming to guide relevant clinical practice. This guideline consists of six sections: application scope of guideline, concepts of craniocerebral surgery-related seizures and epilepsy, postoperative application of ASMs in patients without seizures before surgery, application of ASMs in patients with seizures associated with lesions before surgery, emergency treatment of postoperative seizures, and 16 recommendations.